Handgrip Strength as a Diagnostic Tool in Work-Related Upper Extremity Musculoskeletal Disorders in Women - Deborah Alperovitch-Najenson; Eli Carmeli; Raymond Coleman; Haim Ring (The Scientific World Journal)
The aim of this study was to determine if handgrip strength might be used as a diagnostic tool in musculoskeletal disorders of the upper extremities in women working in an industrial environment. The setting was an electronic factory with four groups of women (n = 101) in a factory assembling electronic components. Handgrip strength was measured using a Jamar® hydraulic hand dynamometer. The study investigated grip strength in managers-engineers, cable wiring, circuit board assembly, integrated circuits women at 90? elbow flexion and 180? elbow extension. Women seeking or receiving medical care for musculoskeletal disorders of the upper extremities or neck showed significant declines (p < 0.01) in handgrip strength and these also related to the type of work and the level of perceived physical exertion. Women in the managerial-engineering group showed fewer musculoskeletal disorders of the upper extremity compared with the other groups and also had significantly stronger handgrip. Our findings encourage us to recommend hand dynamometer testing as a useful diagnostic tool to determine loss of handgrip strength.